2021
DOI: 10.1002/fsn3.2340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frozen storage on the biochemical composition of five commercial freshwater fish species from River Nile, Sudan

Abstract: Postharvest processing and preservation of fish have great influence on fish quality and consumption. Freshwater fish in Sudan are facing problems related to bad handling and improper storage which reduce their quality. This study investigated the changes in the chemical composition, mineral contents, pH and acid value during storage (−18°C) of five commercial fish species (Bagras bayad, Lates niloticus L., Mormyrus casahive L., Oreochromis nilotica L., and Synodrontis schall) from the River Nile coast of Suda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…More specifically, after 120 d, the AV, POV, p-AV, and CDV were 7.62 ± 0.14 mg/g, 23.67 ± 0.55 meq/kg, 2.33 ± 0.03, and 33.57 ± 0.89, respectively. This observed increase in the AV is also consistent with previous studies [ 24 , 25 ] and is closely related to the free fatty acid content [ 26 , 27 ]. Previously, it was reported that the oxidation of fish meat during storage causes the breakage of ester bonds, which releases a large amount of free fatty acids and increases the AV [ 28 ].…”
Section: Results and Analysissupporting
confidence: 93%
“…More specifically, after 120 d, the AV, POV, p-AV, and CDV were 7.62 ± 0.14 mg/g, 23.67 ± 0.55 meq/kg, 2.33 ± 0.03, and 33.57 ± 0.89, respectively. This observed increase in the AV is also consistent with previous studies [ 24 , 25 ] and is closely related to the free fatty acid content [ 26 , 27 ]. Previously, it was reported that the oxidation of fish meat during storage causes the breakage of ester bonds, which releases a large amount of free fatty acids and increases the AV [ 28 ].…”
Section: Results and Analysissupporting
confidence: 93%
“…During defrosting, ice crystals perforate food membranes, leading to exudation of cellular contents [ 41 ] . Different results were obtained by Malik et al [ 42 ], who showed that freezing (−18 °C) increased significantly (P < 0.05) potassium content in Bagrus bayad . Akinwumi [ 50 ] reported that freezing and smoking increased significantly (P < 0.05) potassium content in Clarias gariepinus .…”
Section: Resultsmentioning
confidence: 65%
“…Different results were obtained by Aberoumand [ 41 ] who showed that during freezing, water content decreased in some Iranian coastal fish species. Malik et al [ 42 ] reported that during freezing at −18 °C, moisture content in Lates niloticus decreased significantly compared to that of raw fish. The addition of water during defrosting could explain the increase in water content of frozen fish [ 22 ] .…”
Section: Resultsmentioning
confidence: 99%
“…At 120 d, the AV, POV, p -AV, and CDV were 3.77 ± 0.14 mg/g, 75.16 ± 0.85 meq/kg, 1.94 ± 0.07, and 43.29 ± 0.23, respectively. The increased AV is closely related to the free fatty acid content ( Malik et al, 2021 ). It has been reported that the oxidation of fish oil during storage causes the breakage of ester bonds, releasing a large amount of free fatty acids that increase the AV ( Crexi et al, 2009 ; Zhang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%